Towards a context-aware Wireless Sensor Networks - Aarab, Zineb; El Ghazi, Asmae; Saidi, Rajaa; Driss Rahmani, Moulay (International Journal of Engineering and Technology, 2018)
Recently, the development of wireless sensor networks (WSNs) is spreading rapidly. WSNs are highly distributed self-organized systems which comprise a large number of resource constrained sensor nodes. Developers of WSNs face many challenges from communication, memory, limited energyâ€¦ Also, mobility has become a major concern for WSN researchers. Indeed, Mobile WSNs (MWSN) consist of mobile sensor nodes that can move on their own and also interact with the physical environment. Developing applications for MWSN is a complicated process because of the wide variety of WSN applications and low-level implementation details. Integrating context-awareness can improve MWSN applications results. In this paper, some research issues and challenges involved in the design of WSNs are presented. Model-Driven Engineering offers an effective solution to WSN application developers by hiding the details of lower layers and raising the level of abstraction. In this sense, we propose a context-aware WSN architecture and WSN metamodel to ease the work for developers in this field.Â